Pool Screening: An Example of Independent Nonidentical Bernoulli Trial. Issue 9 (20th October 2016) - Gao, Hongjiang; Aban, Inmaculada; Katholi, Charles R.
Abstract : Pool screening is a widely used study design to make inference about the probability of a subject being positive for an infection when the probability is extremely low. When the pool sizes are unequal, outcomes of pool screening follow independent nonidentical Bernoulli distributions. This paper presents different calculation methods for the probability distribution of T, the number of positive pools. Marcus and Lopes recursive method is recommended.